Feasibility of Non-contrast-enhanced MR Angiography Using the Time-SLIP Technique for the Assessment of Pulmonary Arteriovenous Malformation - HAMAMOTO, Kohei (Magn Reson Med Sci, 2016)
PURPOSE: The purpose of this study was to evaluate the diagnostic performance of non-contrast-enhanced magnetic resonance angiography with time-spatial labeling inversion pulse (time-SLIP MRA) in the assessment of pulmonary arteriovenous malformation (PAVM). METHODS: Eleven consecutive patients with 38 documented PAVMs underwent time-SLIP MRA with a 3-tesla unit. Eight patients with 25 lesions were examined twice, once before and once after embolotherapy. The lesions were divided into two groups—initial diagnosis (n = 35) and follow-up (n = 28)—corresponding to untreated and treated lesions, respectively, and were evaluated separately. To evaluate the initial diagnosis group, two reviewers assessed image quality for visualization of PAVMs by using a qualitative 4-point scale (1 = not assessable to 4 = excellent). The location and classification of PAVMs were also evaluated. The results were compared with those from digital subtraction angiography. For evaluation of the follow-up group, the reviewers assessed the status of treated PAVMs. Reperfusion and occlusion were defined respectively as visualization or disappearance of the aneurysmal sac. The diagnostic accuracy of time-SLIP MRA was assessed and compared with standard reference images. Interobserver agreement was evaluated with the κ statistic. RESULTS: In the initial diagnosis group, time-SLIP MRA correctly determined the PAVMs in all but one patient with one lesion who had image degradation due to irregular breath. Image quality was considered excellent (median = 4) and the κ coefficient was 0.85. Additionally, both readers could correctly localize and classify the PAVMs on time-SLIP MRA images with both κ coefficient of 1.00. In the follow-up group, the sensitivity and specificity of time-SLIP MRA for reperfusion of PAVMs were both 100%, and the κ coefficient was 1.00. CONCLUSION: Time-SLIP MRA is technically and clinically feasible and represents a promising technique for noninvasive pre- and post-treatment assessment of PAVMs.